If -nx2 + tx + c = 0, what is x equal to?

Answers

Answer 1
Answer: f(x)=-nx^2+tx+c=0\n\n \Delta=t^2-4\cdot(-n)\cdot c=t^2+4cn\n\n 1.\n \Delta<0 \Rightarrow x\in\emptyset\n\n 2.\n \Delta=0\n x=(-t)/(2\cdot(-n))=(t)/(2n)\n\n 3.\n \Delta>0\n √(\Delta)=√(t^2+4cn)\n x_1=(-t-√(t^2+4cn))/(2\cdot(-n))=(t+√(t^2+4cn))/(2n)\n x_2=(-t+√(t^2+4cn))/(2\cdot(-n))=(t-√(t^2+4cn))/(2n)\n

Related Questions

An accident victim gets 0.5 pints (pt) of blood and 750 milliliters (mL) of an intravenous (IV) solution. What is the ratio of blood to the intravenous solution in lowest terms?
Which of these conditions might be true if polygons ABCD and KLMN are similar? A. The measures of corresponding angles of ABCD and KLMN are equal, but the lengths of corresponding sides of ABCD are half those of KLMN.B. The measures of corresponding angles of ABCD and KLMN are in the ratio 1 : 2, but the lengths of corresponding sides of ABCD and KLMN are not proportional. C. The lengths of corresponding sides of ABCD and KLMN are equal, but the measures of corresponding angles of ABCD and KLMN are not equal. D. The lengths of corresponding sides of ABCD and KLMN are proportional, but the measures of corresponding angles of ABCD and KLMN are not equal. E.The measures of corresponding angles of ABCD and KLMN are not proportional, but the lengths of corresponding sides of ABCD and KLMN are proportional.
Find the sum of the geometric sequence –3, 15, –75, 375, … when there are 9 terms and select the correct answer below.A. -976,563 B.976,563 C.1,464,843 D.976,562
Hay can someone please help me what's7x4+6-12/4
Complete the statement. –5 + = –5 A.5 B.–5 C.0 D.–1

You have two boxes of colored pens. The first box contains a red pen, a blue pen, and a green pen. The second box contains a yellow pen, a red pen, and a black pen. What is the set that represents all the pens? a.{red pen, blue pen, green pen}
b.{red pen}
c.{red pen, red pen, green pen, yellow pen, black pen}
d.{red pen, blue pen, green pen, yellow pen, black pen}

Answers

Thank you for posting your question here. If you have a  two boxes of colored pens. The first box contains a red pen, a blue pen, and a green pen. The second box contains a yellow pen, a red pen, and a red pen, blue pen, green pen, yellow pen, black pen. The answer is D. I hope it helps. 

Answer:

d. {red pen, blue pen, green pen, yellow pen, black pen}

Step-by-step explanation:

Be

A = Colors of pens in the first box

B = Colors of pens in the second box

A = {red, blue, green}

B = {yellow, red, black}

D =? set that represents all the pens

In set theory, the union of two (or more) sets is an operation that results in another set, whose elements are the same as the initial sets, without repeating those that are the same.

Therefore, the set that represents all the pens is:

D = {red, blue, green, yellow, black}

Hope this helps!

5(7 − 4)2 ÷ 3 + 11 (the 2 is an exponent btw)

Answers

P.E.M.D.A.S
First subtract 4 from the 7 to give you 3.
3 with an exponent of 2 would equal 9. 5 times 9 equals 45 divided by three equals 15 plus 11 equals...

The answer: 26

If RS = 12 and ST = 7, find RT. U

Answers

Answer:

Answer is 19

Step-by-step explanation:

Add 12 and 7 and you will get the Answer 19.

Hope this helps.

A school custodian waxed the gymnasium floor that measured 20 feet by 20 feet. How many square feet did she have to wax?

Answers

Hey there, all you do is multiply 20 by 20, 20×20=400. Therefore, the answer is 400 square feet.

5(t+3)+2(3t+4)-(5t-3)

Answers

5(t+3)+2(3t+4)-(5t-3)
First, you need to use the distributive property.
5t+15+6t+4-5t+3
Next, you add/subtract like terms
5t+6t-5t=6t
15+4+3=22
So, you are left with:
6t+22

Hope this helped! If you have any other questions pertaining to this, please ask!
The answer is 6t + 26                  In the process of solving this problem you will use mathematical properties , adding , subtracting , dividing , and simplifying. 

My reason being is because , 1st you solve | 2 *3t + 13 , than look at the equation again :

it's really , (5*3t) + 2 *( (3t+4) ) - ( 5t - 3 ) .  This is how I got my answer , by pulling out like terms , which happen to be : 6t + 26 = 2 * (3t+13).

The last step to the answer is below :

2 * (3t + 13) .

I really hope that this helps you out a lot, have a nice day :)







Find the inverse of h(x) = (2x + 6)/5

Answers

Answer:

h^-1(x) = (5x - 6)/2

Step-by-step explanation:

To find the inverse of h(x) = (2x + 6)/5, we need to solve for 'x':

y = (2x + 6)/5 ⇒ 5y = 2x + 6 ⇒ 5y - 6 = 2x ⇒ x = (5y - 6)/2

Therefore, h^-1(x) = (5x - 6)/2

Answer:

(5x-6)/2

Step-by-step explanation:

h(x) = (2x + 6)/5

y =  (2x + 6)/5

To find the inverse, exchange x and y

x = (2y+6) /5

Then solve for y

Multiply each side by 5

5x = (2y+6)/5*5

5x = 2y+6

Subtract 6 from each side

5x-6 = 2y+6-6

5x-6 = 2y

Divide by 2

(5x-6)/2 = 2y/2

The inverse is

(5x-6)/2